Andrew Murray’s “Missionary Problem” : addressing the gap between the spiritual and the everyday lives of church members - van Niekerk, Attie (Stellenbosch Theological Journal, 2022)
The article compares two views on the missionary problem: one was expressed in Andrew Murray's book The Key to the Missionary Problem, about 120 years ago. Murray emphasised the low level of the spiritual life of the church as the main missionary problem; the key to solving this problem is the revival of a strong personal spiritual life in all missionaries and in all church members. The second view on the missionary problem has to do with one of the unfinished tasks of the missionary movement that Murray helped to establish. It is tacitly found in the Nova Institute's work over the last 26 years. It is not presented as the key to the missionary problem but as a small effort to contribute to the solving of one of the missionary problems, namely the gap between the spiritual and the everyday lives of church members.